2021
DOI: 10.1134/s002689332102028x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Tick-Borne Encephalitis Virus Genome 5'-UTR from Northern Eurasia

Abstract: This paper reports the analysis of the nucleotide sequences of the 5'-untranslated region (5'-UTR) of tick-borne encephalitis virus (TBEV) genomic RNA isolated from 39 individual taiga ticks collected in several regions of Northern Eurasia. The sequences of 5'-UTRs of the Siberian and Far East TBEV genotypes were 89% and 95% identical to the prototype strains (Zausaev and 205), respectively. The detected nucleotide substitutions were typical for these two TBEV genotypes, which made possible unambiguous identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The TBEV 5ʹUTR has a canonical length of 132 nt throughout all subtypes. Despite conservation of 5ʹUTR length, there is considerable sequence variability that accounts for average sequence identity levels between 89 and 95 per cent for TBEV-Sib and TBEV-FE, respectively ( Ponomareva et al. 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TBEV 5ʹUTR has a canonical length of 132 nt throughout all subtypes. Despite conservation of 5ʹUTR length, there is considerable sequence variability that accounts for average sequence identity levels between 89 and 95 per cent for TBEV-Sib and TBEV-FE, respectively ( Ponomareva et al. 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TBEV 5’UTR has a canonical length of 132 nt throughout all subtypes. Despite conservation of 5’UTR length, there is considerable sequence variability that accounts for average sequence identity levels between 89% and 95% for TBEV-Sib and TBEV-FE, respectively [58]. This heterogeneity at the primary sequence level, however, does not translate into structural diversity.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide synteny analysis of the Senzhang strain and three reference strains (Neudoerfl strain for European subtype [22], 205 strain for Far-Eastern subtype [23,24], and Vasilchenko strain for Siberian subtype [12,25]) showed that the Senzhang strain had high synteny with the other three subtypes. However, there was significant variation at the 3' end of the genome sequence.…”
Section: Synteny Analysis Showed Variation At the 3' End Of The Senzh...mentioning
confidence: 99%